2014
DOI: 10.3892/ol.2014.2760
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of HER2 may improve the outcome of external irradiation therapy for prostate cancer patients

Abstract: Prostate cancer (PCa) is the most common type of cancer among males. Human epidermal growth factor receptor type 2 (HER2) expression in PCa has been reported by several studies and its involvement in the progression towards androgen-independent PCa has been discussed. External irradiation is one of the existing therapies, which has been demonstrated to be efficient in combination with androgen deprivation therapy for the treatment of advanced PCa. However, 20–40% of patients develop recurrent and more aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In a recent in vitro study, Andersson et al . showed that HER2 expression in PC‐3 cells increased significantly after external irradiation leading to resistance to therapy …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a recent in vitro study, Andersson et al . showed that HER2 expression in PC‐3 cells increased significantly after external irradiation leading to resistance to therapy …”
Section: Discussionsupporting
confidence: 91%
“…In agreement with clinical data, antiHER2 treatment did not induce any measurable therapeutic effect, however, IHC HER2 staining demonstrated that even short treatment with trastuzumab eliminated HER2 expression. Interestingly, in agreement with our in vitro data, HER2 expression increased shortly after radiotherapy in the group treated with the radiopeptide but was not detected in the group treated with the combination of radiopeptide and trastuzumab. The absence of HER2 expression shortly after therapy could be attributed to continued saturation of HER2 with trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…A549 non-small cell lung cancer (NSCLC) cell line, which has genomic amplification of EGFR and HER2 and was used to show that NSCLC could benefit from lapatinib treatment (Diaz et al, 2010). PC3 prostate cancer cell line that was used to show that radiation resistant prostate cancers express HER2, and may benefit from HER2 targeted therapy (Andersson et al, 2015). 60 replicate spots were printed for each microenvironment composed of pairwise combinations of four ECM and seven ligands on either 2500 Pa or 40 kPa elastic modulus substrata.…”
Section: Resultsmentioning
confidence: 99%
“…Among further developments of customized radiosensitizers, just those molecularly targeting the identified PCa cell radioresistance-linked individual gene aberrations will enhance the PCa radiation therapy lasting effectiveness (1)(2)(3)(4)(5)(6)(7)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Despite external beam radiation therapy (EBRT) delivery technological advances -from intensity modulated therapy to tomotherapy and image-guided robot 6D radiotherapy, allowing high energy radiation delivery meanwhile minimising side-effects -the prostate cancer (PCa) biochemical/clinical relapse percentage remains nowadays high (post-EBRT PCa recurrence at 20-40 %) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%